Pre-quaternary divergence and subsequent radiation explain longitudinal patterns of genetic and morphological variation in the striped skink, Heremites vittatus - Baier, Felix; Schmitz, Andreas; Sauer-Gürth, Hedwig; Wink, Michael (BMC evolutionary biology, 2017)
Many animal and plant species in the Middle East and northern Africa have a predominantly longitudinal distribution, extending from Iran and Turkey along the eastern Mediterranean coast into northern Africa. These species are potentially characterized by longitudinal patterns of biological diversity, but little is known about the underlying biogeographic mechanisms and evolutionary timescales. We examined these questions in the striped skink, Heremites vittatus, one such species with a roughly longitudinal distribution across the Middle East and northern Africa, by analyzing range-wide patterns of mitochondrial DNA (mtDNA) sequence and multi-trait morphological variation.
Gesehen am 03.08.2017